Strategy for Development of Istiqomah Poterry SMEs in Paseban Village Using the Smart Business Map - Monica Luciana Indriawati; Imanuddin Hasbi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
In the era of increasingly sophisticated digitalization and seeing the support provided by the Indonesian Ministry of Cooperatives and UMKM in full, many MSME players are trying to make changes, one of which is by changing the way of selling which was initially conventional or through offline stores, namely meeting directly with consumers into a system online-based or online store, namely consumers can buy a product or service without having to meet directly with the seller. In this study, we wanted to examine the development strategy for the istiqomah pottery umkm in Paseban village using a smart business map. In this study using qualitative data methods obtained from various sources with various data collection techniques (triangulation) and carried out continuously until saturated.